Subordination in Western Tamang (Patan Pragya, 2022)
This article examines the clause combining in Western Tamang of Nuwakot district in Nepal. The significance of language as spoken in a particular community of Nepal reflects in the diversity as being accommodated in the national policy of language by the language commission of Nepal. Western Tamang is a major dialect of Tamang, a Tibeto-Burman language spoken in Nepal. The main goal of this study has been to analyze the forms and functions of clause combining in Western Tamang. This article describes the process of clause combining from both formal and functional perspectives. The data for this study have been taken from the Western Tamang dialect spoken in Rasuwa and Trishuli based on functional-typological grammar of T. Givón (2001).However; simple clauses are discussed in terms of subordination and coordination to some extent. Subordination involves five kinds of clauses: serial verb construction, complement clauses, adverbial clauses, relative clauses and converbal clauses. In subordination, Western Tamang uses non-finite form of the verb as a major strategy for clause combining. In coordination, except for conjunction and adversative conjunction, it uses coordinators borrowed from Nepali. It uses simple juxtaposition, an asyndeton coordination for conjunction. Clause combining as a morpho-syntactic phenomenon in Western Tamang reveals typologically interesting characteristics which needs from a broad typological perspective. The morpho-syntactic analysis of clause combining in the Western Tamang would contribute to understanding new phenomenon in Western Tamang and other related languages. This study may provide the basic foundation for the further study of the morpho-syntactic aspects in dialect. It is useful to local community for preparing materials for multilingual education in the dialect as well. Despite differences perceived among the Tamang speaking people in terms of language variations, the basics in their language are similar. The beauty and property of language can be seen in diversity.